Including Host Availability and Climate Change Impacts on the Global Risk Area of Carpomya pardalina (Diptera: Tephritidae) - Qin, Yujia; Zhang, Yuan; Clarke, Anthony R.; Zhao, Zihua; Li, Zhihong (Frontiers in Ecology and Evolution, 2021)
Fruit flies are well known invasive species and climate-based risk modelling is used to inform risk analysis of these pests. However, such research tends to focus on already well-known invasive species. This paper illustrates that appropriate risk-modelling can also provide valuable insights for flies which are not yet “on the radar”. Carpomya pardalina is a locally important cucurbit infesting fruit fly of Western and Central Asia, but it may present risk to other temperate countries where melons are grown. MaxEnt models were used to map the risk area for this species under historical and future climate conditions averaged from three global climate models under two Shared Socio-economic Pathways in 2030 and 2070 from higher climate sensitivity models based on the upcoming 2021 IPCC sixth assessment report. The results showed that a total of 46.46% of the world’s land mass is climatically suitable for the fly, it could establish widely around the globe both under current and future climates. Our MaxEnt modelling highlights particularly that Western China, Russia and other European countries should pay attention to this currently lesser-known melon fly, current and expanding melon trade could offer direct invasion pathways to those regions. While this study offers specific risk information on C. paradalina, it also illustrates the value of applying climate-based distribution modelling to species still with limited geographic distributions.